Who says so, who says no: religiosity and heresy - Fiorillo, Marília Pacheco (FCL-UNESP Laboratório Editorial, 2013)
Imagination and enthroned religion are antithetical. Dogma, as the core of monotheist religions, is not more than a methodical and diligent denial to the curiosity, autonomy and inventiveness. It is a asymmetrical relation between the one who ignores, fears and begs, and the Other who knows all and disregards everything which lies in the power of the churches.